Characteristics and Outcomes of 35 Breast Cancer Patients Infected With COVID-19 - Zhang, Bo; Xie, Rong; Hubert, Shawna M.; Yu, Yuanhang; Zhang, Yue; Lei, Xiao; Deng, Wei; Chen, Jianying; Li, Yunqiao (Frontiers in Oncology, 2020)
Since December 2019, a novel coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has rapidly engulfed the world. Cancer patients infected with COVID-19 are considered to carry higher severity of disease and mortality rate than common COVID-19 patients in previous studies. However, due to the poor clinical information on COVID-19 patients with cancer, the evidences supported this conclusion are insufficient. At present, rather limited reports have analyzed the clinical data of breast cancer patients infected with COVID-19. Therefore, in this retrospective study, we described clinical characteristics and outcomes of 35 COVID-19 patients with breast cancer, and compared 55 COVID-19 patients without cancer and 81 COVID-19 patients with other types of cancer as controls. Our data showed that there were no differences in disease severity and outcomes between the COVID-19 patients with breast cancer and common COVID-19 patients, which was contrast to previous studies. In addition, compared with other types of cancer patients, asymptomatic infections and mild cases among breast cancer patients made up a substantially larger proportion. Our results indicated that the clinical characteristics of breast cancer patients were milder than other types of cancer patients, but there was no significant differences in outcomes between the two groups.